School-based education programmes for the prevention of unintentional injuries in children and young people. - Orton, Elizabeth; Whitehead, Jessica; Mhizha-Murira, Jacqueline R.; Clarkson, Mandy; Watson, Michael Craig; Mulvaney, Caroline A.; Staniforth, Joy U.L.; Bhuchar, Munish (Wiley, 2016)
Background: Unintentional injuries are the leading cause of death in children aged four to 18 years and are a major cause of ill health. The school setting offers the opportunity to deliver preventive interventions to a large number of children and has been used to address a range of public health problems. However, the effectiveness of the school setting for the prevention of different injury mechanisms in school-aged children is not well understood.